Paper structure as an inexpensive and easy to use components of temporary shelters - Latka, J. (Видавництво Львівської політехніки, 2011)
Beginning of 21st Century started with large amount of natural and civilization disasters. Thousands of people are bereaved their houses not only as a structures but also as meaning of home. To avoid psychological degradation it is needed to make them feel safe and secure in the minimum level of their existence. To achieve shelters, which could fulfill sense of safety and privacy it is needed to create temporary structures which will be described by: economy, simplicity both in production and construction on the site, lightness, flexibility, durability, pro ecology and aesthetics. One of the materials which can be used to make such shelters is paper. Following article shows examples and advantages of using this material in architecture.
Паперові споруди як недорогі і легкі у використанні елементи тимчасових притулків
Keywords: architecture; paper; homless